The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/jts.20407
|View full text |Cite
|
Sign up to set email alerts
|

Imagery rehearsal therapy for posttraumatic nightmares in U.S. veterans

Abstract: Imagery rehearsal therapy (IRT) may help reduce residual nightmares and posttraumatic stress disorder (PTSD) symptoms in veterans after trauma-focused PTSD treatment. Fifteen male U.S. veterans with PTSD and trauma-related nightmares, who had not previously completed trauma-focused PTSD treatment, attended 6 IRT group sessions. No benefits were observed immediately posttreatment. At 3- and 6-month follow-up, however, trauma-related nightmare frequency (nights/week) decreased (p < .01). The number of trauma-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 14 publications
2
47
0
2
Order By: Relevance
“…Other explanations include problems with our measure of PTSD symptoms (the Posttraumatic Diagnostic Scale; Foa et al, 1997), which has not been specifically validated in veterans, and the possibility that new learning, behavioral change, and symptom improvement may not have an immediate impact on the long-standing sick-role identification associated with the chronic clinical profile of our participants. In support of the latter, although no immediate posttreatment improvements were seen in a pilot study of IRT in veterans, significant changes were observed at 3-and 6-month follow-up (Lu, Wagner, Van Male, Whitehead, & Boehnlein, 2009). …”
Section: Discussionmentioning
confidence: 62%
“…Other explanations include problems with our measure of PTSD symptoms (the Posttraumatic Diagnostic Scale; Foa et al, 1997), which has not been specifically validated in veterans, and the possibility that new learning, behavioral change, and symptom improvement may not have an immediate impact on the long-standing sick-role identification associated with the chronic clinical profile of our participants. In support of the latter, although no immediate posttreatment improvements were seen in a pilot study of IRT in veterans, significant changes were observed at 3-and 6-month follow-up (Lu, Wagner, Van Male, Whitehead, & Boehnlein, 2009). …”
Section: Discussionmentioning
confidence: 62%
“…As compared with other recent studies of PTSD in veterans (Lu, Wagner, Van Male, Whitehead, & Boehnlein, 2009;Rona et al, 2009), both the control and the intervention groups had relatively low PCL scores. One important difference in recruitment is that most other intervention studies required that participants meet full criteria for a diagnosis of PTSD, while in this study, trauma exposure was the standard for inclusion, and 35% of the sample did not exceeded the cutoff score that suggests possible PTSD.…”
mentioning
confidence: 56%
“…In addition, examination of significant clinical change indicated that very few patients in either imagery rehearsal or sleep and nightmare management had meaningful long-term improvement. Given two positive clinical trials indicating the efficacy of imagery rehearsal delivered in group format in other traumatized populations Krakow et al, 2001) and positive findings from uncontrolled pilots of imagery rehearsal with veterans (Forbes et al, 2001;Harb et al, 2009;Lu et al, 2009;Moore & Krakow, 2007;Nappi et al, 2010), an explanation for these non-significant findings was sought. Even though there are certain similarities between this trial and the other two controlled trials of imagery rehearsal Krakow et al, 2001), there are several important distinctions, namely in the choice of comparison conditions, the nature of the patient samples, and the particulars of the respective treatment strategies.…”
Section: Discussionmentioning
confidence: 98%